A proposed model for medical records managing using blockchain: an analytical study (Comprehensive Journal of Science, 2025)
Electronic medical records (EMRs) represent a cornerstone of modern healthcare systems; however,challenges such as data fragmentation in paper and electronic formats, inefficient management,limited accessibility, and security and privacy concerns remain significant obstacles to building anintegrated health system. This paper proposes a blockchain-based model, specifically utilizingHyperledger Fabric, to aggregate patients’ medical records from multiple sources within a unifiedand secure framework. The proposed model leverages blockchain features—transparency,decentralization, and immutability—while granting patients full control over access permissionsthrough a direct consent mechanism implemented via smart contracts and digital signatures.Physicians can request access to a patient’s data, which the patient may approve or reject, whilelaboratory results are shared through private channels to preserve confidentiality and ensureregulatory compliance. The system defines distinct roles for hospitals, insurance companies, and theMinistry of Health in administrative and financial processes without granting direct access tomedical records. A prototype experiment demonstrated the efficiency of the model in enhancingdata protection and achieving transparency, paving the way for broader practical applications. Thepaper also highlights challenges related to system performance, integration with existinginfrastructures, and legal considerations, while outlining the expected impact on improvinghealthcare quality and enabling secure, real-time access to patients’ medical histories
Keywords: Electronic Medical Records (EMRs) ,Hyperledger Fabric ,Smart Contracts ,Healthcare Data Privacy , Access Control Management ,Digital Healthcare